An Empirical Study on the Relationship between Urban Spatial Form and CO2 in Chinese Cities - Yanchun Yi (Sustainability, 2017)
Although several studies have explained the effect of urbanization on China’s carbon emissions, most have focused on population urbanization, while ignoring the urban spatial form. This study investigates the impact of urban spatial form, measured by residential density, on the evolution of carbon emissions of 108 cities from 2003 to 2013 in China. The main results are as follows: (1) although urbanization significantly increases CO2 emissions, urban spatial form measured by residential density produces a negative effect on CO2 emissions in China.; (2) China has not become the “pollution haven” of foreign direct investment (FDI), instead, green FDI has reduced carbon emissions significantly; (3) the environmental dividends of low-carbon transformation have been observed in eastern and middle cities, but not in western ones. Therefore, establishing compact cities and traversing a low-carbon path is both feasible and necessary.